Characterization of Cepharanthin Nanosuspensions and Evaluation of Their In Vitro Activity for the HepG2 Hepatocellular Carcinoma Cell Line - Zhao, Yue; Fu, Tingting; Meng, Gaoke; Qiao, Fangxia; Hou, Yanhui; Liu, Yanhua; Yang, Jianhong (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Conventional cancer therapeutics has enormous toxicity and severe side effects that generate multi-drug resistance. Therefore, an urgent need exists for new alternative therapeutic agents for cancer treatment. Cepharanthin (CEP) has anti-cancer potential but has poor aqueous solubility, which limits its clinical use. Nanosuspensions (NS) are attractive as insoluble drug delivery systems. Objectives: In this study, we used D-alpha Tocopherol acid Polyethylene Glycol Succinate (TPGS), Polyvinylpyrrolidone (PVP) VA64, and Croscamellose Sodium (CCS) as stabilizers to produce TPGS-CEP-NS, PVP VA64-CEP-NS, and CCS-CEP-NS by wet-milling technology, and then characterized the NS and evaluated their functional activities in vitro. Methods: CEP Nanosuspensions (CEP-NS) were prepared by the wet-milling method. The prepared NS were characterized by particle size distribution, zeta potential, morphology, surface properties, and molecular interactions. The NS were evaluated for their effects on HepG2 cells in vitro. The evaluations included assessment of cellular cytotoxicity, cellular apoptosis, NS uptake by cells, and mitochondrial membrane potential changes. Results: CEP-NS showed an appropriate particle size and were physically stable. All CEP-NS exhibited HepG2 enhanced anti-proliferative effects by reducing cell viability, enhanced cellular uptake, induced cellular apoptosis, and mitochondrial membrane potential loss. Conclusions: CEP-NS may be effective therapeutic agents for the treatment of hepatocellular carcinoma.
Keywords: HEPG2